The Oleaginous Yeast Meyerozyma guilliermondii BI281A as a New Potential Biodiesel Feedstock: Selection and Lipid Production Optimization - Ramírez-Castrillón, Mauricio; Jaramillo-Garcia, Victoria P.; Rosa, Priscila D.; Landell, Melissa F.; Vu, Duong; Fabricio, Mariana F.; Ayub, Marco A. Z.; Robert, Vincent; Henriques, João A. P.; Valente, Patricia (Frontiers in Microbiology, 2017)
A high throughput screening (HTS) methodology for evaluation of cellular lipid content based on Nile red fluorescence reads using black background 96-wells test plates and a plate reader equipment allowed the rapid intracellular lipid estimation of strains from a Brazilian phylloplane yeast collection. A new oleaginous yeast, Meyerozyma guilliermondii BI281A, was selected, for which the gravimetric determination of total lipids relative to dry weight was 52.38 % for glucose or 34.97 % for pure glycerol. The lipid production was optimized obtaining 108 mg/L of neutral lipids using pure glycerol as carbon source, and the strain proved capable of accumulating oil using raw glycerol from a biodiesel refinery. The lipid profile showed monounsaturated fatty acids (MUFA) varying between 56 or 74 % in pure or raw glycerol, respectively. M. guilliermondii BI281A bears potential as a new biodiesel feedstock.